Palladium(II) Complex with Tridentate Ligand Containing Pyrenyl Core - Hai, Nguyen Minh; Thu, Tran Thi Tam; Thao, Dinh Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
A series of ligands containing pyrenyl core which are PyEt1 , PyEt2 , and PyEt3 have been successfully synthesized. PyEt2 , a bidentate ligand and PyEt3 , a tridentate ligand were used to prepared Pd(II) complexes by reactions with PdCl 2 (CH 3 CN) 2 . The titled compounds displayed intriguing geometries around the central palladium atoms. 1 H-NMR results showed that palladium in Pd-PyEt3 adopts a five-coordinate configuration. Keywords : Pyrene, palladium, five coordination. References: [1] M. Zhao, X. Zhou, J. Tang, Z. Deng, X. Xu, Z. Chen, X. Li, L. Yang, L.-J. Ma, Pyrene excimer-based fluorescent sensor for detection and removal of Fe3+ and Pb2+ from aqueous solutions, Spectrochim Acta A. 173 (2017) 235-240. https://doi.org/10.1016/j.saa.2016.09.033. [2] H. Turhan, E. Tukenmez, B. Karagoz, N. Bicak, Highly fluorescent sensing of nitroaromatic explosives in aqueous media using pyrene-linked PBEMA microspheres, Talanta. 179 (2018) 107-114. https://doi.org/10.1016/j.talanta.2017.10.061. [3] N. Li, L. Qi, J. Qiao, Y. Chen, Ratiometric Fluorescent Pattern for Sensing Proteins Using Aqueous Polymer-Pyrene/γ-Cyclodextrin Inclusion Complexes, Anal. Chem. 88 (2016) 1821-1826. https://doi.org/10.1021/acs.analchem.5b04112. [4] G. Sivaraman, T. Anand, D. Chellappa, Pyrene based selective-ratiometric fluorescent sensing of zinc and pyrophosphate ions, Anal. Methods. 6 (2014) 2343-2348. https://doi.org/10.1039/c3ay 42057d. [5] D. Fernández, M.I. García-Seijo, T. Kégl, G. Petőcz, L. Kollár, M.E. García-Fernández, Preparation and Structural Characterization of Ionic Five-Coordinate Palladium(II) and Platinum(II) Complexes of the Ligand Tris[2-(diphenylphosphino)ethyl]phosphine. Insertion of SnCl2 into M−Cl Bonds (M = Pd, Pt) and Hydroformylation Activity of the Pt−SnCl3 Systems, Inorg. Chem. 41 (2002) 4435-4443. https://doi.org/10.1021/ic020006k.